Greening the Getaways: Sustainable Tourism Accounting Practices in Bali - Kadek Linda Kusnita; I Wayan Aditya Tariana; Gede Crisna Wijaya; Ni Wayan Merry Nirmala Yani (Astina: Jurnal Ekonomi Utama, 2024)
Sustainable tourism is essential for preserving Bali's natural and cultural heritage amid the rapid growth of its tourism sector. This study explores sustainable tourism accounting practices, emphasizing the integration of green accounting and policy frameworks to mitigate environmental impacts and ensure socio-economic benefits. Key practices include the application of Tri Hita Karana values, carbon labeling, and rooftop solar initiatives, alongside strategies like Penta-Helix collaboration and community empowerment. These initiatives aim to minimize resource depletion, reduce carbon emissions, and promote eco-friendly operations in the hospitality and tourism sectors. Despite substantial progress, challenges such as organizational obstacles, limited digital skills, and a lack of centralized sustainability classifications persist. The COVID-19 pandemic further underscores the necessity of resilient, sustainable models. The findings highlight the importance of holistic approaches combining environmental stewardship with economic growth to maintain Bali's appeal as a global destination. By aligning with sustainable tourism policies and implementing robust green accounting measures, stakeholders can ensure long-term viability while fostering economic prosperity. The research concludes that Bali's sustainable tourism future hinges on strategic collaboration, capacity-building efforts, and adaptive practices that balance environmental, social, and economic priorities. This study provides valuable insights for policymakers, tourism operators, and researchers aiming to advance eco-tourism and sustainable accounting in similar high-demand destinations.